Electroreduction of CO2 on Au(310)@Cu High‐index Facets. Issue 12 (8th February 2023) - Liang, Liang; Feng, Quanchen; Wang, Xingli; Hübner, Jessica; Gernert, Ulrich; Heggen, Marc; Wu, Longfei; Hellmann, Tim; Hofmann, Jan P.; Strasser, Peter
Abstract: The chemical selectivity and faradaic efficiency of high‐index Cu facets for the CO2 reduction reaction (CO2 RR) is investigated. More specifically, shape‐controlled nanoparticles enclosed by Cu hk0 facets are fabricated using Cu multilayer deposition at three distinct layer thicknesses on the surface facets of Au truncated ditetragonal nanoprisms (Au DTPs). Au DTPs are shapes enclosed by 12 high‐index 310 facets. Facet angle analysis confirms DTP geometry. Elemental mapping analysis shows Cu surface layers are uniformly distributed on the Au 310 facets of the DTPs. The 7 nm Au@Cu DTPs high‐index hk0 facets exhibit a CH4 : CO product ratio of almost 10 : 1 compared to a 1 : 1 ratio for the reference 7 nm Au@Cu nanoparticles (NPs). Operando Fourier transform infrared spectroscopy spectra disclose reactive adsorbed *CO as the main intermediate, whereas CO stripping experiments reveal the high‐index facets enhance the *CO formation followed by rapid desorption or hydrogenation. Abstract : Au(310)@Cu truncated ditetragonal prisms (DTPs) enhance the activity and selectivity for CO2 electromethanation. Elemental mapping analysis shows Cu surface layers are uniformly distributed on the Au 310 facets of the DTPs. Operando Fourier transform infrared spectra show reactive adsorbed *CO as the main intermediate. CO stripping experiments reveal the high‐index facets enhance the *CO formation followed by rapid desorption or hydrogenation.